TAPAS ACUPRESSURE TECHNIQUE (TAT) INTERVENSI TEPAT UNTUK MENURUNKAN KECEMASAN PADA PASIEN PREOPERASI. - Rodi Sanjaya, Lalu; Sulistyaningsih (MEDIA ILMU KESEHATAN, 2012)
Background: One of preventive actions performed on patients in hospital is to prevent the occurrence of anxiety. The trigger of the anxiety is often experienced by patients due to surgery procedure. Patients who could not adjust to their anxiety often have difficulty in pre operations, such as sleep disorders, somatic complaints, digestive disorders, urinary disorders, increased blood pressure, and so forth. Anxiety experienced by patients need to be treated with drugs or with alternative therapies, complementary therapies and energy therapies. Tapas Acupressure Technique (TAT) is one of Psychological Energy Therapy (EP) which can be used to balance, restore, and enhance the function of the patient's body by stimulating the energy system in the patient's body. Objective: To determine the effect of TAT on the level of preoperative anxiety in patients in Wates Hospital in Kulon Progo of Yogyakarta. Methods: This was a Quasi-Experimental study with a design of pre test and post test nonequivalen control group. The population in this study was all pre-surgery patients. Samples were taken using accidental sampling technique amounted to 32 (16 intervention and 16 control) in accordance with the criteria. The instrument to measure anxiety was Hamilton Anxiety Rating Scale (HARS). The results were analyzed by two methods, seeing the impact of the intervention on anxiety with Wilcoxon test and comparing the anxiety levels between groups (intervention and control) using Mann Whitney test. Results: A decrease in anxiety levels occurred after TAT intervention was given (pre-test moderate anxiety by 62% and post-test mild anxiety by 69%). Wilcoxon Signed Rank test results in the intervention group obtained p-value of 0.314. The results of post-test anxiety levels with Mann Whitney in the control and intervention group obtained p-value of 0.037. Conclusions: TAT interventions undertaken could reduce the level of patient preoperative anxiety. In providing a good and comprehensive service to patients who will be undergoing surgery, there is a need to give complementary therapies such as energy psychology therapy like TAT. Keywords: Pre-operative patients, anxiety, Tapas Acupressure Technique (TAT)